2020
DOI: 10.7196/ajtccm.2020.v26i3.108
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of pulmonary hydatid cysts in children in KwaZulu-Natal Province, South Africa

Abstract: Background. Pulmonary hydatid cyst disease is still a major problem in countries like South Africa (SA), where livestock farming is common. Hydatidosis has a variable clinical course depending on the size, location and complications of the cyst. For pulmonary cysts of any size, surgery remains the gold standard for treatment, with lung conservation surgery being the ideal. Objectives. To describe the epidemiology, clinical presentation, surgical management, and surgical outcomes of paediatric pulmonary hydatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…[20,21,28] Owing to the blood supply of the portal venous system, the liver is the primary site affected by CE (~70% of cases), followed by the lungs and spleen. [1,15,26,29,[39][40][41] In the present study, the majority of patients (62.5%) had isolated liver involvement. It is worth mentioning that none of the patients with intraperitoneal involvement had previously undergone abdominal surgery for hydatid disease.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…[20,21,28] Owing to the blood supply of the portal venous system, the liver is the primary site affected by CE (~70% of cases), followed by the lungs and spleen. [1,15,26,29,[39][40][41] In the present study, the majority of patients (62.5%) had isolated liver involvement. It is worth mentioning that none of the patients with intraperitoneal involvement had previously undergone abdominal surgery for hydatid disease.…”
Section: Discussionsupporting
confidence: 48%
“…Dogs feeding on infected offal in the vicinity further perpetuate the life cycle and transmission of the parasite to the environment. [20,21] Similarly, Ngcobo et al [26] noted that the majority of pulmonary CE cases in their study were from rural areas of KwaZulu-Natal and Eastern Cape provinces.…”
Section: Discussionmentioning
confidence: 73%
“…Ngcobo et al found 52.4% IHA positivity in ruptured hydatid cysts and 41.2% in non-ruptured hydatid cysts, but they did not find a statistical difference between the two groups [ 1 ]. Özdemir et al found statistically significantly higher IHA positivity in ruptured hydatid cysts in a study of 649 patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hydatid cyst is a zoonotic disease caused by echinococcal tapeworms. Traditionally, it has been reported in Central Asia, the Middle East, the Mediterranean region, East Africa, South America, New Zealand, and Australia due to its endemic nature related to animal husbandry [ 1 ].…”
Section: Introductionmentioning
confidence: 99%